(untitled) (Bangladesh Journal of Anatomy, 2014)
Context: Gestational diabetes is important because of both of its high prevalence and the possible fetal and maternal complications. Gestational diabetes mellitus is well known for its disasterious impact on the fetus in terms of perinatal mortality and morbidity. It has effect on gross morphology and overall structure of umbilical cord. So, the present study was done to observe the effect of gestational diabetes mellitus on morphological structure of umbilical cord. Materials and methods: A cross sectional, analytical type of study was carried out in the department of anatomy, Sher-E-Bangla Medical College, Barisal from June 2008 to June 2009. A total of sixty umbilical cords were collected of which thirty were from mothers having gestational diabetes mellitus and thirty were from mothers not suffering from gestational diabetes mellitus. The samples were divided into two groups as group A (control group) and group B (gestational diabetic group). The umbilical cords were examined to observe its mode of insertion to placenta. Then length and diameter of the umbilical cord were measured. Result: In this study, mode of attachment of umbilical cord to placenta were 7(23.3%), 5(15.7%) in central attachment and 17(56.7%), 21(70.0%) in paracentral attachment in group A and group B respectively. But there were no significant difference between two study groups. The mean length and diameter of the umbilical cord was higher in gestational diabetic group but length variable did not differ significantly(p>0.05)in between two study groups. The mean diameter was significantly (p>0.05) higher in gestational diabetic group than the control group. Bangladesh J. Anat. 2014; 12(2) : 35-39